FAKTOR-FAKTOR YANG BERPENGARUH PADA PROGNOSIS PASIEN TUMOR OTAK METASTASIS DI RSUD SAIFUL ANWAR MALANG - Dotti Inggrianita; Dessika Rahmawati; Rodhiyan Rakhmatiar; Nuretha Hevy Purwaningtyas (PERDOSNI, 2021)
ABSTRACT Introduction: Metastatic brain tumor is a critical period for the spread of malignancy originating from other organs. This type of tumor is the most common intracranial tumor. Prognosis for metastatic brain tumors is poor. Karnofsky Performance scale is an assessment of performance status which can be used to know prognosis of patients with brain tumors. Aim To determine the factors that influence the prognosis of metastatic brain tumor patients in Saiful Anwar General Hospital. Methods: The design of this study was cross sectional retrospective. Data were taken based on patient’s characteristics, clinical, radiological factors, primary tumor type and comorbidities from Neurooncology register data in RSUD dr. Saiful Anwar Malang during January 2017 to December 2020. The data were presented in descriptive and analytic using multivariate logistic regression. Result: There were 71 subjects with metastatic brain tumors and had the same proportion of males and females. Based on the assessed factors, there were two variables that significantly correlated. Age <60 years had a correlation with Karnofsky Performance Scale <60 (p: 0.012) (OR: 0.076). Decreased consciousness had a significant correlation with poor prognosis, that is Karnofsky Performance Scale <60 (p: 0.021) (OR: 13.851). Discussions: Factors affected prognosis of metastatic brain tumor in saiful anwar general hospital malang Age < 60 years and altered mental state affect prognosis of patients with metastatic brain tumor in Saiful Anwar General Hospital. Age < 60 years is a good prognosis while decreased of consciousness shows the poor prognosis. Keywords: Karnofsky performance scale, metastatic brain tumor, prognosis.